Using End of Aya due to Presentation and Delay at Abi Al Soud Explanation - Rababah, Mohammad; Al-Hawari, Mohammad (Jordan Journal of Islamic Studies, 2023)
This study seeks to examine the rhetorical direction of Abi Al Soud explanation when considering the end of Aya due to presentation and delay while contrasting it with the ancient and contemporary linguists. Also, this study attempted to identify the rhetorical purposes of presentation and delay in the end of Aya at Abi Al Soud as stated by him when considering the role of end of Aya. The problem of the study lies in the attempt to answer the following main question: Is the argument of Abi Al Soud in end of Aya consideration due to presentation and delay acceptable? To achieve these purposes, the researchers adopted several approaches, including the inductive approach by tracing the positions of presentation and delay and their explanations by Abi Al Soud as being related to end of Aya consideration; the analytical deductive design by analyzing the arguments of Abi Al Soud and criticizing them and deducting the rhetorical purposes of end of Aya through the statments of ancient and contemporary explainers and linguists. The study concluded with several results, the most important is the systematic out of order for the end of Aya related to apparent presentation and delay was for rhetorical purposes imposed by the semantic and context, and not for confusion of heads of Ayat and the end of the previous Aya.